2015
DOI: 10.29244/jhi.6.3.144-151
|View full text |Cite
|
Sign up to set email alerts
|

Pendugaan Parameter Genetik Vigor untuk Viabilitas dan Vigor Benih Cabai (Capsicum annuum L.) Menggunakan Analisis Setengah Dialel

Abstract: <p>ABSTRACT</p><p><br />The purpose of this study was to estimate the narrow sense heritability (h2ns), broad sense heritability (h2bs), heterosis, and heterobioltiosis, coefficient of genetic variances, coefficient of phenotypic variances, additive and dominant variances. Pepper population used in this study consisted of IPB C2, IPB C9, IPB C10, IPB C15 and half diallel hybrid. To estimate the effect of reciprocal IPB C10 x IPB C2 hybrid was used. Accelerated aging method was used to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
1
0
3
Order By: Relevance
“…Informasi pendugaan parameter genetik sangat diperlukan untuk memperbaiki karakter suatu populasi (Ekowahyuni et al, 2015). Menurut Alia et al (2004), nilai parameter genetik yang diperlukan dalam proses seleksi terdiri dari aksi gen, variabilitas genetik dan heritabilitas.…”
Section: Pendahuluanunclassified
“…Informasi pendugaan parameter genetik sangat diperlukan untuk memperbaiki karakter suatu populasi (Ekowahyuni et al, 2015). Menurut Alia et al (2004), nilai parameter genetik yang diperlukan dalam proses seleksi terdiri dari aksi gen, variabilitas genetik dan heritabilitas.…”
Section: Pendahuluanunclassified
“…Perkecambahan benihmerupakan salah satu indikator yang berkaitan dengan kualitas benih. Pengujian viabilitas harus menggambarkan kecambah yang potensial, jika dengan penanganan yang memadai harus merefleksikan hasil kecambah yang diharapkan pada saat berada dipersemaian (Ekowahyuni et al 2012). Benihyangmemiliki viabilitas rendah akan berakibat terjadinya kemunduran benih yang cepat selama penyimpanan, kecepatan berkecambah benih menurun, serangan hama dan penyakit meningkat, jumlah kecambah abnormal meningkat, danrendahnyaproduksi tanaman (Sadjad, 1981).…”
Section: Pendahuluanunclassified
“…Information about the genetic parameters is necessary to improve the characteristics of a population. Genetic parameters can support breeders in managing an efficient breeding program because of their vital role in enhancing Capsicum annuum L. (Ekowahyuni et al, 2015). Several chili studies have shown that traits can benefit selection criteria with those variables closely associated with yield components and certain vegetative features (Syukur et al, 2010;Istiqlal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%